2021
DOI: 10.1017/wet.2021.68
|View full text |Cite
|
Sign up to set email alerts
|

Response of dry beans to tiafenacil applied preemergence

Abstract: Tiafenacil is a new non-selective, protoporphyrinogen IX oxidase (PPO) – inhibiting pyrimidinedione herbicide that is under consideration for registration in corn, soybean, wheat, cotton, and other crops to control grass and broadleaf weeds prior to crop emergence. The sensitivity of dry beans to tiafenacil is not known. Four field experiments were completed at Exeter and Ridgetown, ON, Canada during the 2019 and 2020 growing seasons to determine the sensitivity of azuki, kidney, small red, and white beans to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Results are similar to other studies in which tiafenacil applied PRE at 25 g a.i. per ha -1 caused 0-4% injury in azuki, kidney, small red, and white bean and caused no adverse effect on plant stand, dry biomass, height, SM content, and yield (Soltani et al, 2021b). Sprague et al (2020) also observed no visible injury, plant stand reduction, or yield reduction with tiafenacil applied PP at 24 g a.i.…”
Section: White Bean Tolerance Studymentioning
confidence: 84%
See 3 more Smart Citations
“…Results are similar to other studies in which tiafenacil applied PRE at 25 g a.i. per ha -1 caused 0-4% injury in azuki, kidney, small red, and white bean and caused no adverse effect on plant stand, dry biomass, height, SM content, and yield (Soltani et al, 2021b). Sprague et al (2020) also observed no visible injury, plant stand reduction, or yield reduction with tiafenacil applied PP at 24 g a.i.…”
Section: White Bean Tolerance Studymentioning
confidence: 84%
“…Control of weeds, especially MHR horseweed has not been consistent with the co-application of glyphosate (C 3 H 8 NO 5 P) + tiafenacil (Soltani et al, 2021b;Westerveld, 2021;Westerveld et al, 2021). Earlier studies have shown that glyphosate + tiafenacil applied PP provides only 51-68% control of MHR horseweed in soybean (Soltani et al, 2021b). The co-application of glyphosate + tiafenacil with bromoxynil (C 7 H 3 Br 2 NO), metribuzin (C 8 H 14 N 4 OS), halauxifen-methyl (C 14 H 11 C l2 FN 2 O 3 ), 2,4-D ester, bromoxynil + metribuzin, bromoxynil + halauxifen-methyl, or bromoxynil + 2,4-D ester applied PP may improve MHR horseweed control.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations